2017
DOI: 10.1200/jco.2017.35.8_suppl.212
|View full text |Cite
|
Sign up to set email alerts
|

Real-world concordance of clinical practice with ASCO and NCCN guidelines for EGFR/ALK testing in aNSCLC.

Abstract: 212 Background: Timely and appropriate biomarker testing guides evidence-based treatment decision-making in advanced non-small cell lung cancer (aNSCLC). American Society of Clinical Oncology (ASCO) and National Comprehensive Cancer Network (NCCN) guidelines recommend that all treatment-eligible patients with non-squamous, or squamous histology in non-smokers undergo EGFR and ALK biomarker testing prior to initiating first line therapy. Genentech’s Learning and Clinical Integration team and Flatiron Health ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…In a study of patients with newly diagnosed mNSCLC recruited from 15 community clinics, only 8% of 814 patients had complete tissue genotyping for all guideline-recommended biomarkers, with almost onethird not tested for EGFR mutations or ALK fusions, 75% untested for ROS1 fusions, and more than 80% untested for the BRAF V600E mutation, MET amplifications or exon 14 skipping alterations, RET fusions, or ERBB2 mutations (8). In a larger study conducted in 166 clinics, 25% of the almost 7,000 patients were not tested for EGFR mutations or ALK fusions (9). In this study, which represents an enriched Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of patients with newly diagnosed mNSCLC recruited from 15 community clinics, only 8% of 814 patients had complete tissue genotyping for all guideline-recommended biomarkers, with almost onethird not tested for EGFR mutations or ALK fusions, 75% untested for ROS1 fusions, and more than 80% untested for the BRAF V600E mutation, MET amplifications or exon 14 skipping alterations, RET fusions, or ERBB2 mutations (8). In a larger study conducted in 166 clinics, 25% of the almost 7,000 patients were not tested for EGFR mutations or ALK fusions (9). In this study, which represents an enriched Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of therapeutic biomarkers to be assessed in patients with newly diagnosed mNSCLC adds time to the clinical evaluation and places strain on tumor tissue availability, especially when biomarkers are assessed in a sequential manner adding additional expense (7). Real-world studies of clinical practice have demonstrated that significant numbers of patients with mNSCLC are not tested for the four guideline-recommended biomarkers with FDA-approved targeted therapies, EGFR exon 19 deletions and L858R mutation, BRAF V600E mutation, ALK fusions, and ROS1 fusions, and the majority are not tested for all eight guideline-recommended biomarkers (8,9). Utilizing comprehensive tissue next-generation sequencing (NGS) has shown promise in the ability to fully assess patients for the recommended biomarkers but remains challenged by tissue availability and the time required for guideline-complete testing.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, median overall survival was lower for patients treated with chemotherapy, including those not tested for EGFRm and ALK, compared with patients treated with targeted therapy: 12.7 vs. 31.8 months, respectively (7). In a real-world analysis of 166 US community oncology practices from January 2014 to August 2015, only 41% and 65% of patients with EGFRm and ALK+ advanced NSCLC, respectively, were treated with targeted therapy when tested after initiation of first-line therapy, compared with 79% and 94% of patients, respectively, treated with targeted therapy when tested before initiation of first-line therapy (54).…”
Section: The Patient Journey In Real-world Clinical Practicementioning
confidence: 99%
“…The implementation of molecular testing at the time of diagnosis in patients with advanced stage and the administration of molecular targeted agents nearly doubles the median of overall survival (OS) of patients with oncogenic-driven NSCLC. Moreover, it prevents the use of ineffective immunotherapies in this subgroup of patients [56]. However, an exhaustive molecular portrait by using a gene sequencing panel or by searching only specific molecular alterations of interest for the…”
Section: Evidence For the Clinical Relevance Of Liquid Biopsy In Routmentioning
confidence: 99%